Comparison of the Therapeutic Effect of the Mini-Open Incision and Conventional Open Neurolysis of the Median Nerve for Carpal Tunnel Syndrome - Feng Hu; Liang Lu; Jianxue Zeng; Duoyu Li; Bin Liu (International Journal of Clinical Practice)
Objective. The aim of this study was to compare the therapeutic effects of the mini-open incision and conventional open surgery for carpal tunnel syndrome (CTS). Methods. The clinical data of 52 patients with CTS treated at the First Affiliated Hospital of the University of Science and Technology of China from October 2020 to February 2022 were retrospectively analyzed. The patients were divided into the conventional open surgery group (28 cases) and the mini-open incision group (24 cases) according to different surgical incisions applied. The incision length, operation time, time until postoperative return to work, and complications were observed in the two groups. The Visual Analog Scale (VAS) for pain at one day, one month, and three months after surgery and the Boston Carpal Tunnel Questionnaire scores before, at one month, and at three months after surgery were compared between the two groups. Results. The incision length, operation time, and time until return to work in the mini-open incision group were all shorter than those in the conventional open surgery group (2.58 ± 0.35 vs. 7.32 ± 0.61 cm, 18.67 ± 2.62 vs. 29.46 ± 3.42 min, and 5.33 ± 1.40 vs. 13.86 ± 2.70 d, respectively), and differences were statistically significant (P < 0.05 in all). The VAS scores in the mini-open incision group were lower than those in the conventional open surgery group at one day and one month after surgery, while the difference in the VAS scores at three months after surgery was not statistically significant between the two groups. There was no statistically significant difference in neurological recovery between the two groups at postoperative follow-ups (P > 0.05). The incidences of postoperative scar hyperplasia and scar pain were higher in the conventional open surgery group than those in the mini-open incision group, and differences were statistically significant (P < 0.05 in both). Conclusion. Mini-open incision surgery for CTS was a safe and reliable procedure with a precise therapeutic effect, minimal surgical trauma, and high postoperative comfort for patients and could achieve enhanced recovery. Trial Registration. This trial is registered with ChiCTR2200064631.